Pathogen safety and characterisation of a highly purified human alpha1-proteinase inhibitor preparation. (May 2017) - Kee, Scott; Weber, David; Popp, Birgit; Nowak, Thomas; Schäfer, Wolfram; Gröner, Albrecht; Roth, Nathan J.
Abstract: Alpha1 -proteinase inhibitor (A1 PI) deficiency is a genetic condition predisposing to emphysema. Respreeza/Zemaira, a therapeutic preparation of A1 PI, is prepared from human plasma. This article describes the purity and stability of Respreeza/Zemaira and the capacity of virus and prion reduction steps incorporated into its manufacturing process. Purity and stability of Respreeza/Zemaira were analysed using established methods. To test pathogen clearance capacity, high levels of test viruses/prions were spiked into aliquots of production intermediates and clearance studies were performed for selected manufacturing steps, under production and robustness conditions, using validated scale-down models. Respreeza/Zemaira had a purity of 99% A1 PI and consisted of 96% monomers. It remained stable after storage for 3 years at 25 °C. Specific activity was 0.895 mg active A1 PI/mg protein. Pasteurisation inactivated enveloped viruses and the non-enveloped hepatitis A virus. 20 N/20 N virus filtration was highly effective and robust at removing all tested viruses, including parvoviruses, to below the limit of detection. Cold ethanol fractionation provided substantial reduction of prions. The manufacturing process of Respreeza/Zemaira ensures the production of a stable and pure product. Taking into consideration the donor selection process, the testing of donations, and the highly effective virus and prion reduction, Respreeza/Zemaira has a high safety margin.